THE IMPACT OF DYNAMIC FACTORS ON THE SUCCESSFUL IMPLEMENTATION OF SAP - Azam, S.M. Ferdous; shukri, Sakinah mohd; Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
Over the years, SAP has grown and evolved to become the world premier provider of client/server business solutions for which it is so well known today. In this paper we will focus on the problem face by selected organization in Malaysia during the implementation stage and you will realize they face almost the same problems. The study mainly established links between factors influencing the implementations of SAP, while in order to analyze the impacts as well as relationships, Project formulation, Implementation development and deployment are the elected independent variables in this study on the dependent variable SAP implementation success. Data has been selected in this study while emphasizing variables of this study, where regression and correlation analysis has been performed in this study. Result shows significance towards the factors that duly influencing the dependent variable of this study, whereas; significant relationship is also ascertained.